Tilt, Decentration, and Internal Higher-Order Aberrations of Sutured Posterior-Chamber Intraocular Lenses in Patients with Open Globe Injuries - Xiangjia Zhu; Yinglei Zhang; Wenwen He; Hongfei Ye; Chunhui Jiang; Yi Lu (Journal of Ophthalmology)
Purpose. To evaluate the tilt, decentration, and internal higher-order aberrations (HOAs) of sutured posterior-chamber intraocular lenses (IOLs) in patients with open globe injuries. Methods. 46 consecutive patients (47 eyes) who underwent transsclerally sutured IOL implantation were enrolled in this prospective cohort study. Nineteen eyes had a history of open globe injury. The tilt and decentration of the IOLs and the visual quality were measured 1 month after surgery. Results. The horizontal tilt and decentration of the IOLs in the open-globe-injury group were significantly higher than those in the control group (both P<0.05). In the open-globe-injury group, the horizontal decentration was significantly greater in the limbus-sclera-involved group (n=11) than in the only-cornea-involved group (n=8, P=0.040). The internal coma, 3rd-order, and total HOA values at pupil sizes of 4 mm (P=0.006) and 6 mm (P=0.013) were significantly higher in the open-globe-injury group than in the controls. Consequently, the optical quality data for the modulation transfer function and the Strehl ratio (all P<0.05) were significantly poorer in the open-globe-injury group. Conclusions. Open globe injuries damage the structural integrity of the eyeball, resulting in more-misaligned sutured IOLs and poorer visual quality.